2021
DOI: 10.1101/2021.10.11.463900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Near-native state imaging by cryo-soft-X-ray tomography reveals remodelling of multiple cellular organelles during HSV-1 infection

Abstract: Herpes simplex virus-1 (HSV-1) is a large, enveloped DNA virus and its assembly in the cell is a complex multi-step process during which viral particles interact with numerous cellular compartments such as the nucleus and organelles of the secretory pathway. Transmission electron microscopy and fluorescence microscopy are commonly used to study HSV-1 infection. However, 2D imaging limits our understanding of the 3D geometric changes to cellular compartments that accompany infection and sample processing can in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 112 publications
1
30
0
Order By: Relevance
“…We have used Contour to segment mitochondria in a recent preprint where we studied how mitochondrial morphology changes during HSV-1 infection. We found that mitochondria transitioned from a heterogenous morphology in uninfected U2OS cells to a more consistently elongated and branched formation as the infection progressed (24) . Contour can be used to segment other cellular compartments based on intensity and width, such as lipid droplets (Fig.…”
Section: Applications Of Contour To Analyse Geometry Of Cellular Compartmentsmentioning
confidence: 79%
See 4 more Smart Citations
“…We have used Contour to segment mitochondria in a recent preprint where we studied how mitochondrial morphology changes during HSV-1 infection. We found that mitochondria transitioned from a heterogenous morphology in uninfected U2OS cells to a more consistently elongated and branched formation as the infection progressed (24) . Contour can be used to segment other cellular compartments based on intensity and width, such as lipid droplets (Fig.…”
Section: Applications Of Contour To Analyse Geometry Of Cellular Compartmentsmentioning
confidence: 79%
“…We have applied Contour to one study, where we investigated how HSV-1 infection alters the morphology of cellular compartments, and we were able to segment mitochondria in multiple tomograms (24) . The dependency on low projection intensity and width for the segmentation does pose some limitations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations